PERANAN MODEL CBL-STEM CONTEXT TERINTEGRASI WORWALL DAN VIDEO INTERAKTIF TERHADAP LITERASI NUMERASI - Hutauruk, Stefany Margaretha; Ardiansyah, Adi Satrio (TRANSFORMASI, 2024)
The challenges of the 21st century require learners to have abilities, one of which is numeracy literacy. However, the facts show that students' numeracy literacy is still low. So, learning innovations are needed that support the development of numeracy literacy. The CBL-STEM Context model integrated with Wordwall and interactive videos can be an alternative in increasing students' numeracy literacy. The purpose of this study is to describe efforts to increase numeracy literacy through the application of Challenge Based Learning (CBL) with STEM Context integrated with Wordwall and interactive videos.The research method used is Systematic Literature Review (SLR) with an analysis technique consisting of three steps, namely: (1) organization, (2) synthesis, and (3) identification. The results showed that CBL model supports meaningful learning process related to STEM Context in daily life. STEM Context, which is a combination of STEM Education and STEM Word integrated into CBL, can train learners to solve contextual problems. Wordwall integration also provides an interactive practice platform to deepen understanding of the material. A part from that, interactive videos are a medium that can visualize big ideas so that learners can more easily analyze, determine strategies and solve problems. The application of this innovation can increase learners' numeracy literacy. Therefore, the implementation of Challenge Based on STEM Context integrated Wordwall and interactive videos can be developed for various concepts in mathematics.